Reception of refugee children in healthcare. Healthcare professionals´ point of view - Elsa Hrund Jensdóttir 1980- (2016)
Reception and treatment of refugees in health care systems are, with increased globalization, a continuous challenge for health care professionals. The aim of this research is to shed light on and identify factors with potential for improvement in the reception and treatment of refugee children and their families in Iceland and Sweden. This is a qualitative study and the results are based on 12 semi-structured interviews with Swedish and Icelandic health care professionals. The results are analyzed using grounded theory and presented in five distinct themes: organization, communication, cultural competence, culture and empathy, prejudice and racism. They indicate a lack of written guidelines in the health care systems for the reception of refugees as well as insufficient knowledge of their and other immigrants´ situation within health care systems. From the interviewees’ standpoint there is a strong will and desire for improvement and a clear wish for health care administrators to revalue their policies and guidelines, with the aim to improve health care services for refugees. The health care systems in Iceland and Sweden need to scrutinize and revise their systems accordingly, material intended for refugees needs to become readily available in different languages, and health care professionals should be offered training linked to their place of work, in order to make all levels of health care culturally competent. Key words: Refugees; Delivery of Health Care; Child; Family; Culture; Cultural Competency; Qualitative Research; Attitude of Health Personnel Með aukinni hnattvæðingu eru móttaka og umönnun flóttamanna í heilbrigðiskerfum sívaxandi áskorun fyrir heilbrigðisstarfsmenn. Markmið þessarar rannsóknar er að varpa ljósi á álagspunkta og þætti sem betur mega fara í móttöku og umönnun flóttabarna og fjölskyldna þeirra á Íslandi og í Svíþjóð. Rannsókn þessi er eigindleg og byggð á tólf hálfstöðluðum viðtölum, sem tekin voru við sænska og íslenska heilbrigðisstarfsmenn. Niðurstöðurnar eru fengnar með notkun ...